Penggunaan Sistem Proses Pengurusan Keselamatan (Process Safety Management System) di Tapak Pembinaan - Zainudin, Amirah Aina; Mohamed, Sulzakimin; Ta Wee, Seow (Research in Management of Technology and Business, 2021)
Employers must emphasize the safety and health of employees involved in construction activities. However, there is no denying that there are still some cases of accidents involving explosions at the oil and gas plant construction site in Malaysia. Developed countries such as the United States and Korea have already applied Process Safety Management systems in industries involving the use of chemicals. However, the system is still unknown to the industry involved in the handling of chemicals in Malaysia. Although this system has the potential to address security problems in high-risk construction sites, but not many studies have been conducted on it in Malaysia. Therefore, this study is an in-depth literature study that aims to identify the benefits, challenges of use and recommendations for the Process Safety Management system applied in construction projects. This study was conducted with the method of collecting secondary data by systematically analyzing 22 journal articles related to the Process Safety Management system at high-risk construction sites. The results obtained show the benefits of this system to the industry that has applied this system, among them is to reduce the number of accidents that occur in construction projects, challenges faced when wanting to apply this system as there are still employers and employees still do not have extensive knowledge about this system and the suggestions given to upgrade this system in the future such as improving every element found in the Process Safety Management. In conclusion, the findings of this study can to some extent provide information about possibility usage of Process Safety Management system in high-risk construction projects.